AB0515 OBESITY AND WEIGHT LOSS IMPACT IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS. (June 2019) - Gigante, Maria Rita; Petricca, Luca; Mario, Clara DI; Paglionico, Anna Maria; Varriano, Valentina; Alivernini, Stefano; Aquilanti, Barbara; Magurano, Maria Rosaria; Tanti, Giacomo; Tolusso, Barbara; Ferraccioli, Gianfranco; Gremese, Elisa
Abstract : Background: Obesity is considered a chronic low-grade inflammatory status due to the release of bioactive substances, as pro-inflammatory cytokines, by the adipose tissue, and it is known negatively affecting some autoimmune inflammatory diseases, like Rheumatoid Arthritis. Few data are available on the role of obesity in Systemic Lupus Erythematosus (SLE) disease. Objectives: To evaluate the distribution of Body Mass Index (BMI) categories in SLE patients and the association between SLE disease activity and BMI groups. Furthermore, to dissect the impact of weight loss in a cohort of overweight/obese SLE patients, evaluated with a multidisciplinary approach. Methods: Consecutive SLE patients, diagnosed according to the 2012 SLICC criteria, were enrolled. Clinical and demographic characteristics, disease duration, BMI category, laboratory indices and current therapies were collected at baseline and at follow-up visits. A subgroup of SLE patients with BMI≥25 Kg/m 2 underwent a scheduled diet under a Nutritionist guide (1200 calories/daily) and Psycologist support when necessary, maintaining the SLE therapy unchanged and were evaluated by a rheumatologist and a nutritionist every 3 months and clinical and laboratory data and the ACR/EULAR core data set were registered at each follow-up(FU) visit. Results: Of the 277 patients (age 42.2±14.4 years, disease duration 8.4±8.0 years, SLEDAI-2K 6.6±7.6, SLICC 1.9±1.5), 47.6% had articular, 32.3% renal, 23.6% neurological and 21.9% had serositic involvement, respectively. Considering the whole cohort, 66 (23.9%) patients had BMI between 25 and 30 Kg/m 2 and 34 (12.3%) a BMI≥30 Kg/m 2 [of which 15 (5.4%) with BMI ≥35 Kg/m 2 ]. Overweight/obese SLE patients were predominantly male (20.0%) with respect to patients with BMI<25 Kg/m 2 (4.5%, p <0.001). Considering the therapeutic regimens, antimalarials treatment was ongoing in 39.4% of overweight SLE patients and in 61.8% of obese SLE patients compared to 28.7% in normal weight SLE patients ( p < 0.001 for overweight and p <0.001 for obese patients), without any significant correlation between BMI and cumulative steroid dose during the follow-up. Considering the whole SLE cohort, cardiovascular events were more frequent in obese patients (14.7%) than in overweight (7.6%) and normal weight (2.9%) SLE patients (ANOVA test: p =0.01). Twenty-nine SLE patients with BMI≥25 Kg/m 2 (BMI: 33.5 ± 5.1 Kg/m 2, age: 47.7 ± 12.3 years, disease duration: 11.9 ± 9.0 years; SLEDAI: 10.5 ± 5.7, SLICC: 1.3 ± 1.1) underwent a scheduled low calories diet. A significant reduction in BMI was observed at 6 and 12 month follow-up [6.6 ± 5.7% at 6 months FU ( p = 0.001) and 7.0 ± 7.2% at 12 months FU ( p =0.002), respectively] as well as a reduction in disease activity [SLEDAI at 6 months FU: 4.5 ± 4.0 (p=0.001) and at 12 months FU (0.7 ± 0.9 (p <0.001)]. Finally, a significant decrease of systemic inflammatory markers as C-Reactive Protein ( p <0.05) was observed in SLE patients who achieved >5% weight loss compared to SLE patients who did not. Conclusion: Obesity represents a modifiable factor for improving outcomes among obese SLE. A weight loss obtained with a controlled diet may reduce cardiovascular events and reduce the state of chronic inflammation subtended by the activity of adipose tissue. Disclosure of Interests: Maria Rita Gigante: None declared, Luca Petricca: None declared, Clara Di Mario: None declared, Anna Maria Paglionico: None declared, Valentina Varriano: None declared, Stefano Alivernini Speakers bureau: BMS, Barbara Aquilanti: None declared, Maria Rosaria Magurano: None declared, Giacomo Tanti: None declared, Barbara Tolusso: None declared, Gianfranco Ferraccioli Speakers bureau: BMS, Roche, Elisa Gremese Consultant for: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer, Speakers bureau: BMS, Speakers bureau: Roche, Speakers bureau: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Sanofi, UCB, Roche, and Pfizer